Cyclin A2 Protein Overexpression Is Not Caused by Gene Amplification in Colon Cancer. (29th August 2012) - Sørby, Lise Aagaard; Jonsdottir, Kristin; Beiske, Klaus; Blom, Peter; Bukholm, Ida Rashida Khan; Jacobsen, Morten Bj.
Abstract : Increased expression of cyclin A2 protein has been detected in different types of cancers. However, its prognostic importance appears to differ between tumours. The significance and precise mechanisms behind cyclin A2 overexpression remain to be elucidated. We used real-time PCR to examine CCNA2 amplification in tumour cells isolated by laser microdissection and in total tumour tissue in colon cancer patients in which overexpression of cyclin A2 protein had been revealed by immunohistochemistry (n = 22 patients). The results were verified by FISH. CCNA2 amplification was not detected in either the isolated tumour cells or the total tumour tissue. We verified our methods by demonstrating amplification of CCNA2 by real-time PCR in three out of eight breast tumours that overexpressed cyclin A2 protein (this frequency is consistent with the findings of others). However, FISH did not reveal any CCNA2 amplification in the breast tumours, but it did reveal polysomy of chromosome 4 or segments of chromosome 4 in three tumour tissue samples, indicating the importance of verifying the real-time PCR results with another method. To conclude, the increased cyclin A2 protein expression in these patients could not be explained by CCNA2 amplification in isolated colonic tumour cells.